Strategi Pengembangan Wakaf Produktif dalam Sektor Pendidikan: Studi Kasus di Yayasan Wakaf Sahid Husnul Khotimah (YWSHK) Bogor Jawa Barat - Mursyidah, Azizah (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
According to the Ministry of Religious Affairs in the book Bimas Islam in (BIDA) 2016, there are 435,768 Waqf properties in Indonesia with an area of 4.347.021.170 M2. Of the total number of sites, about 75% are already certified and about 10% have economic potential. it can be productively developed. One of the most important waqf sectors is education, as waqf not only supports the development of science but also provides various facilities needed by students, but also provides various facilities needed by students and the community society. This research aims to develop a sustainable strategy through the education sector in Modern Sahid Islamic Boarding School in Bogor, West Java. The Research This research uses qualitative descriptive method. The result of this research shows that that the Sahid Khusnul Khatimah Waqf Foundation, implements 3 systems for productive Waqf productive. Namely: 1) Ijarah / Lease Agreement 2) Management Managed Akad 3) Akad Profit Sharing. From the results of this analysis, it is hoped that the education sector at the Sahid Khusnul Khatimah Waqf Foundation will continue to be sustainable and developed.